2013
DOI: 10.1080/10803548.2013.11076973
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Safety Climate Model in Metal Processing Industries: A Replication Study

Abstract: safety climate safety climate model safety performance replication study metal processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Concerning the descriptive results among German healthcare professionals working in acute care, our data showed lower safety participation scores compared with the safety compliance scores. These results are similar to other studies that have used the same instrument [26,28]. The original instrument developed and published by Neal et al distinguished between safety activities that are part of the job (safety compliance) and activities that support the broader environmental context (safety participation) [22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Concerning the descriptive results among German healthcare professionals working in acute care, our data showed lower safety participation scores compared with the safety compliance scores. These results are similar to other studies that have used the same instrument [26,28]. The original instrument developed and published by Neal et al distinguished between safety activities that are part of the job (safety compliance) and activities that support the broader environmental context (safety participation) [22].…”
Section: Discussionsupporting
confidence: 87%
“…Kaleth and colleagues tested a Persian safety performance scale among Iranian employees of a petrochemical complex and reported a high internal consistency [25]. Similar results were reported by Braunger and colleagues, who tested the instrument as well as the model in Austria [26]. Gracia and colleagues underline their findings for the Spanish setting [27].…”
Section: Introductionsupporting
confidence: 54%
“…So far, the effect of training on safety personnel has been investigated in many studies, and it has been confirmed that training improves safety behavior [55][56][57][58][59] and reduces accidents [60][61][62][63]. Accident experience is another factor affecting the perception of risk, which was placed in the first group in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, safety climate research has consistently presented a conceptual focus on collective phenomena, including both a focus on group and organizational level analyses (Griffin and Curcuruto, 2016). However, the present research, as the original study of Griffin and Neal (2000) and others that used their approach (i.e., Braunger et al, 2013) adopted an individual level to consider safety climate. In fact, our evidences can be compared with their work and a more-broad literature, focused on social-exchange mechanisms, entailed by LMX, which are typically related on the individual perception of the employees’ personal relationships with the organization and supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a motivated worker is willing to put an extra effort for safety and attributes a special value to safety behaviors (Neal and Griffin, 2006). On the other hand, safety knowledge is presented as the extent to which employees have a clear idea of safety processes and correct procedures and behaviors (Braunger et al, 2013). Griffin and Neal (2000) considered safety knowledge and motivation (Mariani et al, 2015) determinants of safety performance and mediators between safety climate and safety performance too.…”
Section: Theoretical Frameworkmentioning
confidence: 99%